2019
DOI: 10.1080/15389588.2019.1679551
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Swedish and Dutch accident data on cyclist injuries in cyclist-car collisions

Abstract: Objective: To reduce the number of severe injuries sustained by cyclists in crashes with vehicles, it is important to understand which kinds of injuries are occurring to identify what should be assessed by means of virtual testing. Method: A detailed analysis of injuries was made based on Swedish and Dutch accident data. The most frequently injured body regions and the most frequent single injuries of these body regions were analysed. Results: Cyclists most frequently injured their heads, upper and lower extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…Head injuries were less frequent for cyclists in the Swedish dataset. This might be a result of high helmet wearing rates ( Otte et al, 2015 ; Leo et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Head injuries were less frequent for cyclists in the Swedish dataset. This might be a result of high helmet wearing rates ( Otte et al, 2015 ; Leo et al, 2019a ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides sex, age has also been identified as an important factor affecting the types and severity of injuries ( Davis, 2001 ; Niebuhr et al, 2016 ; Leo et al, 2019a ; Saadé et al, 2020 ). Davis and Niebuhr et al conclude that elderly pedestrians (≥60YO) tend to suffer more severe injuries than younger pedestrians.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To investigate cyclist casualty rates in developed countries in Europe, Leo et al analysed injuries to cyclists due to traffic accidents based on traffic accident data from Sweden and the Netherlands [21]. Otte et al compared and analysed data on injuries sustained by traditional cyclists and moped riders and concluded that wearing helmets can effectively reduce injuries and mortality rates [27].…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, the death rate of moped-related accidents reached 8% of the total traffic accidents in 2016. Moreover, accident and fatality rates of traditional bikes are high in other large cities in Europe [21]. Therefore, understanding the characteristics of mopeds to improve traffic conditions has become an urgent problem that remains to be solved by traffic management agencies.…”
Section: Introductionmentioning
confidence: 99%